2017
DOI: 10.1080/14397595.2017.1366092
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of six-week extended dosing interval with tocilizumab therapy in a prospective cohort as remission maintenance in patients with rheumatoid arthritis

Abstract: A six-week extended dosing interval of TCZ for patients with RA in sustained remission is proposed as an acceptable treatment option for maintaining efficacy and tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
3
9
0
1
Order By: Relevance
“…By contrast, sustained remission following cessation of TCZ treatment was much lower: in the DREAM study (13), drug free remission or LDA was present in 35.1%, and 13.4% of patients after 24 and 52 weeks respectively following cessation of TCZ used in monotherapy, and in the ACT-RAY study, the remission rate dropped to 16% after stopping TCZ (28). In our study, we observed that a majority (61.5%) of our patients remained in remission at month 24 and 46.1% had successful long-term maintenance following the tapering of TCZ infusions, results that are comparable to those of previous studies (14,25,26).…”
Section: Characteristics Of Patientssupporting
confidence: 90%
See 1 more Smart Citation
“…By contrast, sustained remission following cessation of TCZ treatment was much lower: in the DREAM study (13), drug free remission or LDA was present in 35.1%, and 13.4% of patients after 24 and 52 weeks respectively following cessation of TCZ used in monotherapy, and in the ACT-RAY study, the remission rate dropped to 16% after stopping TCZ (28). In our study, we observed that a majority (61.5%) of our patients remained in remission at month 24 and 46.1% had successful long-term maintenance following the tapering of TCZ infusions, results that are comparable to those of previous studies (14,25,26).…”
Section: Characteristics Of Patientssupporting
confidence: 90%
“…weeks for RA patients in sustained remission for the previous 3 months appeared to provide an acceptable option, with 88% retaining remission after 54 weeks (14). Similarly, Saiki et al published two studies on extending the RTI for TCZ infusions.…”
Section: Characteristics Of Patientsmentioning
confidence: 98%
“…Concerning TCZ tapering, several strategies have been tried, including discontinuation TCZ infusions [12,13], and gradually increasing the RTI to a fixed interval (eg. 6-weeks) [14,[25][26][27]. We conducted the present study to determine if tapering TCZ by progressively increasing the spacing of infusions would be a better strategy to maintain TCZ-treated patients in remission.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that TCZ could induce drug-free remission in a low proportion of patients [12,13]. However, few data reporting the efficacy and safety of TCZ tapering are available and the follow-up of patients is short (less than one year) [14]. We hypothesized that increasing the interval or spacing between TCZ infusions, rather than abruptly stopping treatment in RA patients with remission, may represent a better strategy to reduce the risk of flare.…”
Section: Introductionmentioning
confidence: 99%
“…Иная ситуация складывается в случае достижения неактивного статуса болезни. Исследования при РА у взрослых пациентов, достигших ремиссии, продемонстрировали возможность увеличения интервала между инфузиями ТЦЗ до 6 нед [19]. В исследовании E.A.…”
unclassified